2007
DOI: 10.1038/sj.bjc.6604018
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and functional defects of blood dendritic cells in early- and late-stage breast cancer

Abstract: The generation of antitumour immunity depends on the nature of dendritic cell (DC) -tumour interactions. These have been studied mostly by using in vitro-derived DC which may not reflect the natural biology of DC in vivo. In breast cancer, only one report has compared blood DC at different stages and no longitudinal evaluation has been performed. Here we conducted three cross-sectional and one one-year longitudinal assessments of blood DC in patients with early (stage I/II, n ¼ 137) and advanced (stage IV, n ¼… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
46
1
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 38 publications
10
46
1
1
Order By: Relevance
“…High levels of spontaneous DC apoptosis have also been observed in breast cancer patients, with its significance being unclear [15,16]. Our study indicates that DC apoptosis in cancer patients may play a role in suppressing immune responses against the tumor by inducing immunosuppression and tolerance.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…High levels of spontaneous DC apoptosis have also been observed in breast cancer patients, with its significance being unclear [15,16]. Our study indicates that DC apoptosis in cancer patients may play a role in suppressing immune responses against the tumor by inducing immunosuppression and tolerance.…”
Section: Discussionmentioning
confidence: 70%
“…Our study indicates that DC apoptosis in cancer patients may play a role in suppressing immune responses against the tumor by inducing immunosuppression and tolerance. Therefore, prevention of DC apoptosis may enhance the therapeutic effects of chemotherapy in tumor eradication [15,16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The accumulating progenitor cells are suppressive to several aspects of T cell-mediated immunity and do not efficiently develop into Agpresenting dendritic cells (DCs), thus impeding presentation of tumor-derived Ags to T cells (1)(2)(3). Several studies demonstrated that accumulation of immature myeloid cells and the absence of mature DCs result in accelerated tumor growth and poor outcome in human and murine cancers (1,(3)(4)(5)(6). Therefore, understanding the regulation of myeloid cell differentiation, in particular with regard to the development of DCs, may provide novel therapeutic targets (2).…”
mentioning
confidence: 99%